Screening and identification of miRNAs regulating Tbx4/5 genes of Pampus argenteus - Cheng Zhang; Shun Zhang; Mengdi Liu; Yajun Wang; Danli Wang; Shanliang Xu (PeerJ, 2022)
Background Silver pomfret (Pampus argenteus) is one of the most widely distributed and economically important pelagic fish species. However, an unique morphological feature of P. argenteus is the loss of pelvic fins, which can increase the energy requirement during food capture to some extent and is therefore not conducive to artificial culture. Tbx4/5 genes are highly conserved regulatory factors that regulate limb development in vertebrates and are in turn regulated by microRNAs (miRNAs). However, the miRNAs that directly regulate the Tbx4/5 genes in P. argenteus remain to be elucidated. Methods The Tbx4/5 genes of P. argenteus were first cloned, and the small RNA transcriptomes were sequenced by high-throughput sequencing during the critical period of the fin development at days 1, 7, and 13 of hatching. The miRNAs regulating the Tbx4/5 genes of P. argenteus were subsequently predicted by bioinformatics analysis, and the related miRNAs were verified in vitro using a dual fluorescence reporter system. Results A total of 662 miRNAs were identified, of which 257 were known miRNAs and 405 were novel miRNAs were identified. Compared to day 1, 182 miRNAs were differentially expressed (DE) on day 7, of which 77 and 105 miRNAs were downregulated and upregulated, respectively, while 278 miRNAs were DE on day 13, of which 136 and 142 miRNAs were downregulated and upregulated, respectively. Compared to day 13, four miRNAs were DE on day 7, of which three miRNAs were downregulated and one miRNA was upregulated. The results of hierarchical clustering of the miRNAs revealed that the DE genes were inversely expressed between days 1 and 7, and between days 1 and 13 of larval development, indicating that the larvae were in the peak stage of differentiation. However, the number of DE genes between days 7 and 13 of larval development was relatively small, suggesting the initiation of development. The potential target genes of the DE miRNAs were subsequently predicted, and Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses of target genes were performed. The results suggested that the DE miRNAs were involved in growth, development, and signal transduction pathways, of which the Wnt and Fgfs signaling pathways are known to play important roles in the growth and development of fins. The results of dual fluorescence reporter assays demonstrated that miR-102, miR-301c, and miR-589 had a significant negative regulatory effect on the 3′-UTR of the Tbx4 gene, while miR-187, miR-201, miR-219, and miR-460 had a significant negative regulatory effect on the 3′-UTR of the Tbx5 gene. Altogether, the findings indicated that miRNAs play an important role in regulating the growth and development of pelvic fins in P. argenteus. This study provides a reference for elucidating the interactions between the miRNAs and target genes of P. argenteus in future studies.